Effects of spatially variable plant available water on optimal corn seeding rate – field scale and site-specific approaches - Haag, Lucas A. (Kansas State University, 2008)
Spatial variability in plant available water can be caused by uncontrollable factors such as topography and soil texture as well as controllable factors such as residue management. Research located on the High Plains evaluated the impact of wheat (Triticum aestivum L.) stubble height on snow catch, plant available water at seeding, and optimal corn seeding rates. Treatments consisted of stripper harvest height of 71 cm (28 in.), cut heights of 25 cm (10 in.), and 10 cm (4 in.) Measured snow depths were significantly different among treatments (p<0.0001) with equivalent precipitation of 5.77 (2.27), 3.25 (1.28), and 1.73 cm (0.68 in.) for the stripped, 25 cm, and 10 cm heights respectively. Available soil water at planting increased 24% as stubble height increased from 10 to 71 cm (4 to 28 in) in one year of the study. Two corn hybrids of varying maturity (97 and 108 days) were planted into the stubble treatments at seeding rates ranging from 2.47 to 5.43 plants m[superscript]-2 (10 to 22 000 plants ac[superscript]-1). In the dry year, the long season hybrid responded positively to increasing population in tall stubble and negatively in short stubble. Yield of the short season hybrid increased with increasing stubble height and was mostly unresponsive to population. Grain yields of both hybrids responded positively to increasing plant population in a wet year. Treatments also affected the yield components of yield plant[superscript]-1, kernel weight, and kernels plant[superscript]-1. Managing seeding rates for uncontrollable factors was attempted with small-plot and field scale research across 3 fields in northeast Kansas. A relationship between soil electro-conductivity (EC) and measured water holding capacity values was developed for one study field. This quadratic relationship was significant (p<0.0001) and explained variability in water holding capacity with respect to EC quite well (R[superscript]2=0.6239). Responses from small plots showed that sites differing in population response characteristics could be identified. Field scale data was used to derive a function describing optimal seeding rate with respect to soil EC. In the field under study, optimal seeding rates varied from 3.08 to 8.74 plants m[superscript]-2 (12 500 to 35 375 plants ac-1).
Keywords: variable rate seeding; corn; stubble height; snow catch; soil EC; wheat stubble; Agriculture, Agronomy (0285); Engineering, Agricultural (0539)